If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + -1(15x + -1) = 2(7x + -16) * x Reorder the terms: -5 + -1(-1 + 15x) = 2(7x + -16) * x -5 + (-1 * -1 + 15x * -1) = 2(7x + -16) * x -5 + (1 + -15x) = 2(7x + -16) * x Combine like terms: -5 + 1 = -4 -4 + -15x = 2(7x + -16) * x Reorder the terms: -4 + -15x = 2(-16 + 7x) * x Reorder the terms for easier multiplication: -4 + -15x = 2x(-16 + 7x) -4 + -15x = (-16 * 2x + 7x * 2x) -4 + -15x = (-32x + 14x2) Solving -4 + -15x = -32x + 14x2 Solving for variable 'x'. Combine like terms: -15x + 32x = 17x -4 + 17x + -14x2 = -32x + 14x2 + 32x + -14x2 Reorder the terms: -4 + 17x + -14x2 = -32x + 32x + 14x2 + -14x2 Combine like terms: -32x + 32x = 0 -4 + 17x + -14x2 = 0 + 14x2 + -14x2 -4 + 17x + -14x2 = 14x2 + -14x2 Combine like terms: 14x2 + -14x2 = 0 -4 + 17x + -14x2 = 0 Begin completing the square. Divide all terms by -14 the coefficient of the squared term: Divide each side by '-14'. 0.2857142857 + -1.214285714x + x2 = 0 Move the constant term to the right: Add '-0.2857142857' to each side of the equation. 0.2857142857 + -1.214285714x + -0.2857142857 + x2 = 0 + -0.2857142857 Reorder the terms: 0.2857142857 + -0.2857142857 + -1.214285714x + x2 = 0 + -0.2857142857 Combine like terms: 0.2857142857 + -0.2857142857 = 0.0000000000 0.0000000000 + -1.214285714x + x2 = 0 + -0.2857142857 -1.214285714x + x2 = 0 + -0.2857142857 Combine like terms: 0 + -0.2857142857 = -0.2857142857 -1.214285714x + x2 = -0.2857142857 The x term is -1.214285714x. Take half its coefficient (-0.607142857). Square it (0.3686224488) and add it to both sides. Add '0.3686224488' to each side of the equation. -1.214285714x + 0.3686224488 + x2 = -0.2857142857 + 0.3686224488 Reorder the terms: 0.3686224488 + -1.214285714x + x2 = -0.2857142857 + 0.3686224488 Combine like terms: -0.2857142857 + 0.3686224488 = 0.0829081631 0.3686224488 + -1.214285714x + x2 = 0.0829081631 Factor a perfect square on the left side: (x + -0.607142857)(x + -0.607142857) = 0.0829081631 Calculate the square root of the right side: 0.287937776 Break this problem into two subproblems by setting (x + -0.607142857) equal to 0.287937776 and -0.287937776.Subproblem 1
x + -0.607142857 = 0.287937776 Simplifying x + -0.607142857 = 0.287937776 Reorder the terms: -0.607142857 + x = 0.287937776 Solving -0.607142857 + x = 0.287937776 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.607142857' to each side of the equation. -0.607142857 + 0.607142857 + x = 0.287937776 + 0.607142857 Combine like terms: -0.607142857 + 0.607142857 = 0.000000000 0.000000000 + x = 0.287937776 + 0.607142857 x = 0.287937776 + 0.607142857 Combine like terms: 0.287937776 + 0.607142857 = 0.895080633 x = 0.895080633 Simplifying x = 0.895080633Subproblem 2
x + -0.607142857 = -0.287937776 Simplifying x + -0.607142857 = -0.287937776 Reorder the terms: -0.607142857 + x = -0.287937776 Solving -0.607142857 + x = -0.287937776 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.607142857' to each side of the equation. -0.607142857 + 0.607142857 + x = -0.287937776 + 0.607142857 Combine like terms: -0.607142857 + 0.607142857 = 0.000000000 0.000000000 + x = -0.287937776 + 0.607142857 x = -0.287937776 + 0.607142857 Combine like terms: -0.287937776 + 0.607142857 = 0.319205081 x = 0.319205081 Simplifying x = 0.319205081Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.895080633, 0.319205081}
| 7(x+2)=4[x-(6-x)] | | 7-4t=-8+t | | 5c+2c=4c+18 | | 4(3r-4)=2(7r+5) | | 3j+13=12j-5 | | 5+2x+x^2+y= | | 27+9v=-8(7v-4) | | -5(2y-5)-y=-4(y-2) | | 11j+12=12j-6 | | -0.03x=0.03 | | 4x-3=4(x+9) | | 10*25*y=100000 | | 2(x-1)+(5x+2)+2x=180 | | -72=-2+5m | | 3m-10=3(4m-5) | | 50c^3-25c^2-18c+9=0 | | 5x+16=2(2x+4) | | 4k^2-8k+12=0 | | (2x+10)(2x-3)=4x^2-14 | | 6(5-8v)+12=44 | | 37x+14=6(6x+2) | | 5x+74=3(7x-6) | | F=3r+5 | | -h-1=3h+15 | | 9+5w-14w=12-w | | 5.8m=145 | | 3x+72x= | | -2x+3=4x | | 5(3x-9)-3=5(x-2)+32 | | -5x+7=15 | | -7y+39=2(y+6) | | 5x-8x+9=x-8+17 |